CONSORT 2010 Statement: extension to randomised pilot and feasibility trials - Eldridge, S; Chan, C; Campbell, M; Bond, C; Hopewell, S; Thabane, L; Lancaster, G; PAFS Consensus Group (BMJ Publishing Group, 2016)
The CONSORT Statement (CONsolidated Standards for Reporting Trials) is a reporting guideline designed to improve the transparency and quality of the reporting of randomised controlled trials (RCTs). In this article, we present an extension to the CONSORT Statement for randomised pilot and feasibility trials conducted in advance of a future definitive RCT. The checklist applies to any randomised study in which a future definitive RCT, or a part of it, is conducted on a smaller scale, regardless of its design (eg cluster, factorial, cross-over) or the terms (eg pilot, feasibility, trial, study) used by authors to describe the study. The extension does not directly apply to internal pilot studies built into the design of a main trial, non-randomised pilot and feasibility studies, or phase II studies but these studies all have some similarities to randomised pilot and feasibility studies and so many of the principles may also apply to these studies. The development of the extension was motivated by the growing number of studies described as feasibility or pilot studies, and by research that has identified weaknesses in their reporting and conduct. We followed recommended good practice to develop the extension, including performing a Delphi survey, holding a consensus meeting and research team meetings, and piloting the checklist. Pilot and feasibility randomised studies differ from other randomised trials in their aims and objectives. Consequently, though much of the information to be reported in these trials is similar to that in RCTs assessing effectiveness and efficacy, there are some key differences in the type of information and in the appropriate interpretation of standard CONSORT reporting items. We have retained some of the original CONSORT Statement items, but most have been adapted, some removed, or new items added. The new items cover how participants were identified and consented; if applicable, pre-specified criteria used to judge whether, or how, to proceed with future definitive trial; if relevant, other important unintended consequences; implications for progression from pilot to future definitive trial including any proposed amendments; and ethical approval/research review committee approval confirmed with reference number. This article includes the 26-item checklist, a separate checklist for the abstract, a template for a CONSORT flow chart for these studies, and explanation of the changes made and examples to support this explanation. We believe that routine use of this proposed extension to the CONSORT Statement will eventually result in improvements in the reporting of pilot trials.